Between The Secular And The National: Representations Of Jerusalem In The Media Coverage Of FATAH-affiliated Palestine Satellite Channel - Ihab Ahmed Ra'Uf Awais; Wesam Almahallawi; Osama Kanaker; Mohammed Oklah Abughazlih; Abeer Z.A. Alhosary (Multi-knowledge Electronic Comprehensive Journal For Education And Science Publications (MECSJ), 2024)
Non-Indexed Publication